LEVERAGING GRAMMAR GAMES FOR ELT: A SYSTEMATIC REVIEW - Zifa Eka Putri; Ririn Yusrini Mudawamah; Nafan Tarihoran (Integrative Perspectives of Social and Science Journal, 2025)
Grammar teaching plays an important role in English Language Teaching (ELT), yet traditional methods often fail to engage students effectively. This systematic literature review aims to synthesize empirical research on the use of grammar games in ELT, focusing on their effectiveness, challenges and pedagogical implications. Following PRISMA guidelines, this study analyzed research articles from databases such as Scopus, ERIC, ScienceDirect, and Taylor & Francis Online. Out of 857 identified studies, 20 studies met the inclusion criteria for further analysis. Findings suggest that grammar games improve engagement, motivation, and retention, although challenges such as assessment limitations and teacher preparedness remain. This review highlights gaps in long-term impact studies and suggests future research directions to optimize the integration of grammar games in ELT.